Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Matematika Materi Diagram Batang Pada Peserta Didik Kelas IV di SD Negeri Lidah Kulon I 464 Surabaya - Hatijatul Monaweroh; Herry Purnomo; Asri Susetyo Rukmi (Departement of Mathematics Education, 2023)
This research started with the problem of low learning outcomes of class 4 B students at SD Negeri Tongue Kulon 1 464 Surabaya, in mathematics, especially in bar chart material. In this study there were 28 students, but only 24 students were involved in the research. This is because in the implementation of this study there were 4 students who did not enter. In mathematics, especially in bar chart material, only 9 students out of 24 students who obtained KKTP scores below the minimum score of 68 obtained a percentage of 36% of students. This research is a collaborative classroom action research (collaborative PTK between students, tutor teachers and field supervisors). This research was conducted in two cycles. As a solution to these problems, researchers used the application of the Problem Based Learning (PBL) learning model. Based on the results of the research and discussion, it can be concluded that the application of the Problem Based Learning (PBL) learning model provides a positive response to the learning process and can increase the activity of teachers and students in the learning process, and can also improve student learning outcomes in mathematics, especially diagram material. stem. Student learning outcomes have increased from pre-cycle to cycle I and cycle II. The learning outcomes before the action that reached the KKTP score above the value of 68 were only 9 students with a percentage of 36%. Then in cycle I students who achieved KKTP scores above 68 were 19 students with a percentage of 79%. As well as in cycle II students who achieved KKTP scores above 68 were 22 students with a percentage of 91%.